Comparative Study of Direct and Graphite-Mediated Oxidation of Large PAHs - Weippert, Juergen; Huber, Philipp; Hauns, Jakob; Narita, Akimitsu; Muellen, Klaus; Amsharov, Konstantin; Boettcher, Artur; Kappes, Manfred M. (Journal of Physical Chemistry C, 2021)
We have used a surface-science-based, ion-beam-soft-landing approach to study the heterogeneous oxidation of a series of large polycyclic aromatic hydrocarbons (PAHs) deposited onto highly oriented pyrolytic graphite (HOPG). The reactivities of well-defined thin films of hexabenzocoronene (C42H18), pentacene (C22H14), fullerene precursor (C60H30), and rubrene (C42H28) with effusive beams of oxygen atoms were compared to the reaction outcome upon depositing a monolayer of the same PAHs onto a preoxidized graphite surface. In both cases, sublimable oxidized derivatives of PAHs were observed using mass-resolved temperature-programmed desorption (with compositions assigned using oxygen isotope labeling where necessary). For all PAHs investigated, the on-top oxidation of multilayers leads to epoxides. By contrast, the products of the oxidation of (sub)monolayers are seen to depend on the molecular structure of the PAH. While the flatly adsorbing planar PAHs react to form lactones and quinones, the highly nonplanar rubrene does not show analogous surface-mediated chemistry, instead forming epoxides exclusively. These observations when taken together with our previous study of coronene oxidation are of potential interest for sp2-nanocarbon-based oxidation catalysis. Furthermore, we have demonstrated a ultra high vacuum (UHV)-based route to sublimable oxides ranging in size up to C60H30O5, which may be useful for nanotechnological applications.
CRIS-Team Scopus Importer:2022-04-14